Urban landfills investigation for leachate assessment using electrical resistivity imaging in Johor, Malaysia - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Muhammad Farhan, Zolkepli (Elsevier, 2021)
The use of the electrical resistivity imaging (ERI) approach has expanded dramatically in engineering applications over the years due to the efficiency of the technique in terms of time, expense, and data coverage. The assessment was carried out using ERI to assess the landfill leachate's pollution level at Simpang Renggam, Johor, Malaysia. The ERI survey was carried out in the research region, utilizing the ABEM Terrameter LS 2 equipment using the Schlumberger electrode configuration. Besides, seven (7) parameters of leachate characterization such as Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD5), Suspended Solid (SS), Power of Hydrogen (pH), Ammonia Hydrogen (NH3-N), Turbidity and Biodegradability Ratio (BOD5/COD) were also performed to identify and evaluate the current leachate condition of the landfill. Furthermore, the study, which involves the measurement of the apparent resistivity of the subsurface materials were able to determine the existence of chemical pollutants in the soil at 1.5 m to 4.0 m depth, with special reference to the chemically apparent resistivity linked with the low resistivity anomalies of 1 – 10 Ωm. Based on the investigations conducted, the physiochemical and microbial analysis of the Simpang Renggam leachate site was found to be 1633 mg/L (Chemical Oxygen Demand), 137.41 mg/L (Biological Oxygen Demand), 359.8 mg/L (Suspended Solid), 7.61 (Power of Hydrogen), 385.29 (Ammonia Hydrogen), 117.65 (Turbidity) and 0.07 (Biodegradability Ratio) which shows that all of the parameter's value exceeded the value as stated in the local standard which is Environmental Quality Act (1974) except for the pH value which is within the range value as stated in the standard. The leachate from dumps was thought to arise due to system failures in accepting and managing trash, which was exacerbated by the recent high rains. In hindsight, the ERI result was practical for identifying leachate and, therefore, can benefit the authorities in immediate action to halt the extensive water disturbance at the research region.